6(p-1)+11=17

Simple and best practice solution for 6(p-1)+11=17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(p-1)+11=17 equation:



6(p-1)+11=17
We move all terms to the left:
6(p-1)+11-(17)=0
We add all the numbers together, and all the variables
6(p-1)-6=0
We multiply parentheses
6p-6-6=0
We add all the numbers together, and all the variables
6p-12=0
We move all terms containing p to the left, all other terms to the right
6p=12
p=12/6
p=2

See similar equations:

| 7(f-1)-8=4(f+2)+1 | | x^​3+120+2x=360 | | -3x-4/2=13 | | x3+120+2x=360 | | (x-3)/4=2.5 | | C(4+x)=6 | | −5(x+8)+2x= | | −5(x+8)+2x=59 | | 3-(x+3)=5-2x | | 9w+8=15 | | 4x/2-4=10x-58 | | (p-400)/100=6 | | (p-400)/100=3 | | 3,6-9x=1,8 | | 5(x2+1)=50 | | 2(2t-3)=69t+2) | | 4x–x+31=43 | | 5(4w+8)/3=7 | | 4y+1=y+19 | | -2(x+4)=3(x-5) | | 6-3.5x=2-1,5x | | -2(x+4)=3(x+5) | | t2+7t+10=0 | | 10(s-9)=138 | | 5(-x+2)=-(3x-4) | | 3x+5=(x+5)*2 | | 3r+6=-12 | | 2u+1=-17 | | 2-b+1=8 | | 4e+9=33 | | 2x/3-1/4-2=x | | 10x-3=5x+32 |

Equations solver categories